PERCEPTIONS OF BENEFITS AND SECURITY ON CONFIDENCE AND DECISIONS IN USING DIGITAL WALLET APPLICATIONS (E-WALLET) IN PEKANBARU CITY - Achmad Tavip Junaedi; Astuti Dara Anjeli; Nicholas Renaldo; Suhardjo Suhardjo; Aulia Ramadhani; Indri Yovita (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This research aims to determine and analyze the influence of perceived benefits and security on trust and decision-making of e-wallet users in the city of Pekanbaru. The population of this study comprises all e-wallet application users in Pekanbaru, with a sample size of 200 users as respondents. The sampling technique employed is non-probability sampling, specifically accidental sampling. Data collection is conducted through the use of a questionnaire. Data analysis is carried out using Structural Equation Modeling Partial Least Square (SEM-PLS). The results of the study indicate that perceived benefits and security have a positive and significant impact on trust among e-wallet users in Pekanbaru. Additionally, perceived benefits have a positive and significant influence on the decision-making of e-wallet users in Pekanbaru, while security has a small, insignificant effect on decisions in Pekanbaru City. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh persepsi manfaat dan keamanan terhadap kepercayaan serta pengambilan keputusan pengguna e-wallet di Kota Pekanbaru. Populasi penelitian ini mencakup seluruh pengguna aplikasi e-wallet di Pekanbaru, dengan jumlah sampel sebanyak 200 responden. Teknik pengambilan sampel yang digunakan adalah non-probability sampling, khususnya accidental sampling. Pengumpulan data dilakukan melalui penyebaran kuesioner, sedangkan analisis data menggunakan metode Structural Equation Modeling Partial Least Square (SEM-PLS). Hasil penelitian menunjukkan bahwa persepsi manfaat dan keamanan berpengaruh positif dan signifikan terhadap kepercayaan pengguna e-wallet di Pekanbaru. Selain itu, persepsi manfaat juga berpengaruh positif dan signifikan terhadap pengambilan keputusan pengguna e-wallet di Pekanbaru, sedangkan keamanan memiliki pengaruh positif namun tidak signifikan terhadap keputusan di Kota Pekanbaru.